Feasibility and reliability of evaluate PD‐L1 expression determination using small biopsy specimens in non‐small cell lung cancer. Issue 17 (21st July 2021) - Chen, Minjiang; Xu, Yan; Zhao, Jing; Li, Ji; Liu, Xiangning; Zhong, Wei; Wang, Mengzhao
Abstract: Background: Programmed cell death ligand‐1 (PD‐L1) is a useful biomarker in non‐small cell lung cancer (NSCLC) patients who would probably benefit from immunotherapy. In most patients with advanced stage NSCLC, only small biopsy specimens were available for the evaluation of PD‐L1 expression. In this study, we evaluated the feasibility and reliability of PD‐L1 testing on small biopsy samples. Methods: Small specimens of advanced NSCLC patients obtained via endobronchial ultrasound‐guided transbronchial needle aspiration (EBUS‐TBNA), endobronchial biopsy (EBB), or computed tomography (CT)‐guided core‐needle biopsy were collected. Tumor cell count and tissue sufficiency for PD‐L1 immunohistochemistry (IHC) were evaluated and compared. The clinical course of patients who received immunotherapy in the study population was also examined. Results: Tissue acquisitions for PD‐L1 testing in three groups were all above 90%, with no statistically significant differences. The PD‐L1 expressions levels were concordant in most patients with more than one sample (8/11). In the EBB group, PD‐L1‐positive patients had higher objective response rate (ORR) (53.2% vs. 26.9%, p  = 0.048) and longer progression‐free survival (PFS) (312 vs. 179 days, p  = 0.035) than PD‐L1 negative patients. In the core needle biopsy group, patients with positive PD‐L1 expression also trended to have higher ORR and longer PFS. However, in the EBUS‐TBNA group, both ORR and PFS were similar between patients with positive or negative PD‐L1 expression. Conclusions: This study showed that EBUS‐TBNA, EBB, and core needle biopsy provides adequate samples for PD‐L1 testing. The predictive value of PD‐L1 expression on different small samples still warrants further studies. Abstract : The predictive value of PD‐L1 expression tested on different specimens were compared. The PFS in positive and negative PD‐L1 expression patients in computed tomography (CT) guided core‐needle biopsy, transbronchial biopsy (EBB), and endobronchial ultrasound‐guided transbronchial needle aspiration (EBUS‐TBNA) group were 354 vs 195 days ( p  = 0.410), 312 vs. 179 days ( p  = 0.035), 213 vs. 192 days ( p  = 0.594) separately.